DAMPAK PENERAPAN SERTIFIKASI HASIL TANGKAPAN IKAN DI UNI EROPA TERHADAP EKSPOR IKAN INDONESIA KE BELANDA - Handry, Fatrik; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to clarify the impact on Fisheries of Indonesia export value to the European Union in particular in the Netherlands since imposed its regulations the Minister of marine and fisheries of the Republic of Indonesia number per 28/download/2009 on certification of results catch of fish.In this study the author uses the perspective of liberalism. In his view the interdependence and cooperation promote liberalism. To bridge the problems leading to the author's hypothesis using level analysis of nation-state (nation-State). For more entry into the case impact certification catches against Indonesia fishery export value. the author uses the theory of international trade by david ricardo posited that comparative advantage was the basis in carrying out trade internasiona ...Indonesia applying certification catches to ensure the quality of the catch of fishermen Indonesia as well as anticipate the action Illegal, Unregulated and Unreported Fishing (IUU-Fishing). Through the application of sertifiksi fish catches would be beneficial, improve export competitiveness of fisheries Indonesia also increase the trust of Eu countries in particular the Netherlands to conduct fisheries cooperation with Indonesia.Keywords: Catches Certification System, Illegal Unregulated and Unreported Fishing (IUU-Fishing), the impact, the EU exports